Metals and female reproductive toxicity. (July 2015) - Sengupta, P; Banerjee, R; Nath, S; Das, S; Banerjee, S
Research into occupational exposure of metals and consequences of reproductive systems has made imperative scientific offerings in the preceding few decades. Early research works focused on possible effects on the reproductive functions rather than the complete reproductive health of the woman. Later, it was realized that metals, as reproductive toxins, may also induce hormonal changes affecting other facets of reproductive health such as the menstrual cycle, ovulation, and fertility. Concern is now shifting from considerations for the pregnant woman to the entire spectrum of occupational health threats and thus reproductive health among women.